Implementasi Customer Relationship Management Dalam Mempertahankan Loyalitas Pelanggan Di Masa Kopi - Baihaki, Abdillah; Sari , Eka Anisa (Jurnal Impresi Indonesia, 2025)
The coffee shop industry in Yogyakarta has experienced very rapid growth in the past decade, making it the city with the highest number of coffee shops in Indonesia. Changes in people's lifestyles, especially among young people and students, have also encouraged the increase in coffee consumption and the proliferation of coffee shops with diverse concepts and services. One of the coffee shops that is trying to survive in this competition is Masa Kopi. This study aims to examine how the implementation of Customer Relationship Management (CRM) plays a role in maintaining customer loyalty in the Coffee Age. This research uses a qualitative approach with a descriptive type, where data is obtained through in-depth interviews, direct observation, and documentation of service and promotional activities in the Coffee Period. The results of the study show that CRM in Masa Kopi is carried out through several main strategies, namely improving service quality, offering competitive prices, and providing a pleasant consumption experience. Promotional strategies such as "Morning Coffee Promotion", beauty classes, and nail art are concrete examples of the implementation of price-based CRM to attract customers at a certain time. It was also found that customer satisfaction resulting from service that meets or exceeds expectations has a significant impact on customer loyalty and trust. Thus, the implementation of CRM in Masa Kopi has proven to be effective in building long-term relationships with customers and maintaining business continuity in the midst of high competition in the coffee industry in Yogyakarta.